Encrusters maintain stable carbonate production despite temperature anomalies among two inshore island reefs of the Pilbara, Western Australia - Dee, S.; Cuttler, M.; Cartwright, P.; McIlwain, Jennifer; Browne, Nicola (ELSEVIER SCI LTD, 2021)
Encrusting reef organisms such as crustose coralline algae (CCA), serpulid worms, bivalves, bryozoans, and foraminifera (collectively termed encrusters) provide essential ecosystem services and are a critical part of the reef framework. Globally, research into in situ growth and carbonate production of encrusters has focused on clear water fore-reef settings in the Pacific and Caribbean, with limited studies being conducted on marginal reef systems or within the Indian Ocean. Here we examined spatial and temporal variation in CCA coverage (%) and total encruster carbonate production rates (g cm−2 yr−1) across two inshore turbid island reefs of northern Western Australia. We recorded average carbonate production rates of 0.039 ± 0.002 g cm−2 yr−1, which are comparable to healthy reef sites globally. Our results show variation in lateral CCA cover over small spatial scales, with a strong seasonal signature, while constant average carbonate production rates were maintained. Additionally, we recorded in situ water temperatures above predicted coral bleaching threshold of 29 °C for four weeks and found annual patterns of sea surface temperature anomalies (SSTA) of 2 °C or more being a regular occurrence over the hotter months. Encrusters on these reefs are considered to have a vital contribution to the reef carbonate budgets, and if they maintain stable carbonate production through periods of SSTA, they may support net positive reef carbonate budgets.